Study of near miss cases in obstetrics and maternal mortality in Bastar, Chhattisgarh, India - Bansal, Mamta; Lagoo, Jyoti; Pujari, Khushbu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: According to millennium development goals (MDG) in 2015, the goal number five was to improve the maternal health is falling way below our target. Our aim in reducing maternal mortality by 75% has not been met with MDG. Pregnant women’s health status is not reflected by mortality indicators alone hence the concept of severe acute maternal morbidity (SAMM) is an apt for the present health providing system. The main objectives of the study were to; (1) To determine the frequency of maternal near miss, maternal near miss incidence ratio (MNMR), maternal near miss to mortality ratio and mortality index; (2) To compare the nature of near miss events with maternal mortality; (3) To observe the trend of near miss events. Methods: It was a retrospective study design conducted at Late B.R.K.M Government medical college, Jagdalpur, Chhattisgarh, India during September 2013 to August 2014. The study population includes near miss cases and maternal deaths. Cases were defined based on WHO criteria 2009. Results: Out of 3539 deliveries, 39 wear near miss cases during the study period. The maternal near miss incidence ratio was 11.9/1000 live births, maternal near miss to mortality ratio was 2.05:1, and mortality index was 32.7%. Hemorrhage was the leading cause (43.5%), followed by severe anemia (15.38%), rupture uterus (15.38%), preeclampsia/eclampsia (12.82%), sepsis (5.12%), complicated malaria (5.12%) and hepatitis (2.56%). Maternal mortality ratio (MMR) was 580/100000 live births. Conclusions: Hemorrhage was the leading cause of near miss events. As near miss analysis indicates the quality of health care, it is worth presenting in national indices.